1979
DOI: 10.1111/j.1365-2125.1979.tb00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance Studies With Diazepam and Its Hydroxylated Metabolites

Abstract: 1 Visuo-motor coordination has been used to study the immediate and residual effects of benzodiazepines on performance in man. The technique provides dose and time response data related to the decrement and the persistence of impaired performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Psychomotor tests have revealed no residual impairment the morning after taking up to 30 mg temazepam at night (e.g. Nicholson, 1979), and daytime studies have found that significant psychomotor effects persist for no longer than 4 h after a 40 mg dose (Pleuvry et al, 1980). Similar findings have come from daytime psychometric studies of drowsiness, coordination etc (Matejcek et al, 1983), EEG changes (Matejcek et al, 1983) and maximum velocity of saccadic eye movements (Bittencourt et al, 1981).…”
Section: Introductionsupporting
confidence: 62%
“…Psychomotor tests have revealed no residual impairment the morning after taking up to 30 mg temazepam at night (e.g. Nicholson, 1979), and daytime studies have found that significant psychomotor effects persist for no longer than 4 h after a 40 mg dose (Pleuvry et al, 1980). Similar findings have come from daytime psychometric studies of drowsiness, coordination etc (Matejcek et al, 1983), EEG changes (Matejcek et al, 1983) and maximum velocity of saccadic eye movements (Bittencourt et al, 1981).…”
Section: Introductionsupporting
confidence: 62%
“…Adaptive tracking An adaptive tracking test (Nicholson, 1979) was used to assess eye hand coordination and effects on attention as described earlier (Cohen et al, 1984b). The test lasted for 10 min and was performed in an air conditioned laboratory with standardised lighting.…”
Section: Performance Testsmentioning
confidence: 99%
“…Adaptive tracking (Nicholson, 1979), saccadic and smooth pursuit eye movements (Tedeschi et al, 1983;Norris, 1971;Bittencourt et al, 1981b), and body sway (Scott et al, 1982) have all been shown to be affected by sedative drugs. It is not known however if these tests are sensitive to drug induced ataxia.…”
mentioning
confidence: 99%
“…The adaptive tracking task is a more refined pursuit and tracking test, which has been shown by Borland & Nicholson (1974) to be sensitive to the effects of heptabarbitone 200, 300 and 400 mg, and Nicholson (1979) Other visuo-motor tasks e.g. the automated rotated designs test (Sambrooks, Macculloch, Birtles & Smallman, 1972: Sambrooks, Macculloch & Rooney, 1975 and the continuous performance reading task (Stern, Bremer & McClure, 1974) have been used too infrequently for any estimate of their sensitivity to drug induced changes in performance to be made.…”
Section: Gross Body Movementmentioning
confidence: 99%